Resisting reform? water profits and democracy - Urs, Kshithij; Whittell, Richard (SAGE, 2009)
'Resisting Reform?' looks at the attempts that have been made to 'reform' Bangalore's water supply, situating them in their global and national context and that of the city's broader development. The authors argue that treating water as a commodity is a dangerous principle for any water service, public or private